Thomas Taylor, the Platonist : Selected Writings - Taylor, Thomas, 1758-1835 (Book collections on Project MUSE., 2019)
This volume makes available to the modern reader selected writings of Thomas Taylor, the eighteenth-century English Platonist. TO Taylor we are indebted for the first full translation into English of Plato and Aristotle. Platonism, as Taylor saw it, was an informing principle, transmitted through a "golden chain of philosophers," a doctrine received by Socrates and Plato from the Orphic and Pythagorean past and transmitted to the future. It emerged again and again, enriched in the School of Alexandria, in Renaissance art, in the works of Spenser, Shelley, Yeats. Kathleen Raine is well known as a poet. GEorge Mills Harper is Professor of English, University of Florida. Bollingen Series LXXXVIII. Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905